2002
DOI: 10.1128/iai.70.5.2576-2582.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia-Macrophage Interactions: Host Cell Responses toRickettsia akariandRickettsia typhi

Abstract: The existence of intracellular rickettsiae requires entry, survival, and replication in the eukaryotic host cells and exit to initiate new infection. While endothelial cells are the preferred target cells for most pathogenic rickettsiae, infection of monocytes/macrophages may also contribute to the establishment of rickettsial infection and resulting pathogenesis. We initiated studies to characterize macrophage-Rickettsia akari and -Rickettsia typhi interactions and to determine how rickettsiae survive within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
2
45
0
2
Order By: Relevance
“…Moreover, intact R. typhi particles were detectable in the areas of macrophage infiltration by histological staining, indicating bacterial replication and incapability of these cells to kill R. typhi. In line with these findings, R. typhi has been shown to survive and to replicate in murine and human macrophages (73,74), which is also true for other rickettsiae, such as O. tsutsugamushi (18,19) and Rickettsia akari (75). Therefore, it is not clear whether these cells are recruited to the CNS for defense against R. typhi by phagocytosis and killing of intracellular particles or whether they may serve as a kind of shuttle.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, intact R. typhi particles were detectable in the areas of macrophage infiltration by histological staining, indicating bacterial replication and incapability of these cells to kill R. typhi. In line with these findings, R. typhi has been shown to survive and to replicate in murine and human macrophages (73,74), which is also true for other rickettsiae, such as O. tsutsugamushi (18,19) and Rickettsia akari (75). Therefore, it is not clear whether these cells are recruited to the CNS for defense against R. typhi by phagocytosis and killing of intracellular particles or whether they may serve as a kind of shuttle.…”
Section: Discussionsupporting
confidence: 60%
“…We propose that infection of nonendothelial cells has been overlooked during prior examinations of SFG Rickettsia pathogenesis and that our newly developed techniques have allowed a more complete analysis of infection. This idea is supported by several in vitro and ex vivo studies that have demonstrated that rickettsial species can infect and grow within macrophages and hepatocytes (30)(31)(32)(33), suggesting that the interaction with cells other than those of the endothelium may be an important and underappreciated aspect of the pathogenesis of rickettsial diseases. Additionally, IHC and immunofluorescence microscopy both display intact bacilli, and nonendothelial cells frequently contain multiple plasmid-transformed R. conorii bacteria ( Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Mycobacterium species, Legionella pneumophila, Listeria monocytogenes and mammalian rickettsiae are pathogens which have evolved strategies to avoid eradication by macrophage bactericidal mechanisms [24][25][26][27][28]. Among other survival strategies, mycobacteria prevent acidification of the phagosome and phagosome-lysosome fusion, thereby precluding digestion by lysosomal contents [26,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%